2005
DOI: 10.1002/cncr.21011
|View full text |Cite
|
Sign up to set email alerts
|

Fostering coping and nurturing hope when discussing the future with terminally ill cancer patients and their caregivers

Abstract: BACKGROUNDIt is challenging for clinicians to foster coping and allow hope when discussing prognosis and end‐of‐life (EOL) issues with terminally ill cancer patients and their caregivers. To the authors' knowledge, little research evidence is currently available to guide clinical practice.METHODSThe authors conducted focus groups and individual interviews with 19 patients with far advanced cancer and 24 caregivers from 3 palliative care (PC) services in Sydney, and 22 PC health professionals (HPs) from around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
0
15

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(295 citation statements)
references
References 32 publications
(32 reference statements)
14
266
0
15
Order By: Relevance
“…Other research has shown that most patients want their oncologists to be willing to talk about death and dying [25,59] and cite emotional support as an important physician skill to help them cope when discussing the future [8]. Unfortunately, factors such as disease stage do not predict whether patients want to talk about end-of-life issues [41], so there is no reliable way to predict whether a given patient has concerns about death and dying.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that most patients want their oncologists to be willing to talk about death and dying [25,59] and cite emotional support as an important physician skill to help them cope when discussing the future [8]. Unfortunately, factors such as disease stage do not predict whether patients want to talk about end-of-life issues [41], so there is no reliable way to predict whether a given patient has concerns about death and dying.…”
Section: Discussionmentioning
confidence: 99%
“…En estas circunstancias los profesionales de la salud, pueden desear (consciente o inconscientemente) persuadir al paciente hacia estas acciones, y cada persuasión puede llegar a ser parte de la discusión de la mala noticia. Los profesionales deben ser conscientes de sus intenciones de persuasión y explicitarlas al paciente 31,34,35 . -Minimizar el estrés del paciente: escuchar malas noticas puede ser abrumador emocionalmente para el paciente, y los profesionales pueden exacerbar este estrés si entregan de mala manera dicha noticia 36 .…”
Section: Habilidades Comunicacionalesunclassified
“…Los factores que pueden influenciar la satisfacción son la discusión, proveer responsividad a las emociones del paciente e involucrar al mismo en la toma de decisiones. -Mantener el optimismo del paciente: promover el optimismo del paciente 35,40 , el cual puede ser un poderoso predictor de adaptación y recuperación 41 aunque debe ser balanceado con honestidad y realismo 39,40 . -Minimizar el discomfort del profesional de la salud: el objetivo final del profesional de la salud debe ser minimizar su propio discomfort con la tarea, el cual puede resultar en miedo a la reacción al paciente, a sus propias emociones, a su falta de competencia o miedo a ser cul-pado 42 .…”
Section: Habilidades Comunicacionalesunclassified
“…Objective truths are static and in agreement with fact or reality, whereas subjective truths are based on a person's experience and are continuing and dynamic. Only a few studies have declared what they actually mean when they are asking patients about the truth in prognostic discussions (Clayton et al, 2005a(Clayton et al, , 2005b. What does it mean to patients when they are given a terminal prognosis?…”
Section: Introductionmentioning
confidence: 99%